Optimizing Software Performance: Methodologies, Best Practices, and Modern Tools for Effective Testing (Journal of Artificial Intelligence & Research, 2024)
Performance testing is critical for ensuring the reliability, scalability, and responsiveness of software applications in today’s technology-driven environment. This article provides an in-depth review of various performance testing methodologies, including load, stress, scalability, and endurance testing, each addressing specific aspects of software performance. It emphasizes the importance of realistic test scenarios using synthetic and real user data and explores modern tools and technologies like cloud-based platforms, containerization, and continuous integration. The challenges of performance testing, such as simulating real-world user behavior and analyzing complex systems, are discussed, along with mitigation strategies that stress the importance of cross-functional collaboration and iterative refinement. This comprehensive review offers valuable insights for software practitioners and researchers to effectively implement performance testing strategies, ultimately contributing to the development of robust and high-performing software systems. Results: The performance testing tools were classified according to their relevance in the literature, highlighting the most commonly used tools, their supported input approaches, workload approaches, monitored metrics and logging strategies.